PENGARUH PENDAPATAN DAN KEPERCAYAAN TERHADAP MINAT MEMBAYAR ZAKAT PADA BADAN AMIL ZAKAT NASIONAL (BAZNAS) KABUPATEN KAUR (STUDI PADA ZAKAT MAAL BIDANG PERTANIAN DI DESA PAJAR BULAN) - Neni Seftiani; Yosy Arisandy; Katra Pramadeka (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2026)
This research aims to determine the effect of income on interest in paying agricultural zakat, the influence of trust on interest in paying agricultural zakat, the influence of income and trust together on interest in paying agricultural zakat and to find out how much influence income and trust have on interest in paying agricultural zakat at BAZNAS Kaur Regency. This research uses quantitative data methods collected through distributing questionnaires. The technique used in this research was a saturated sample of 25 people who met the criteria, namely muzakki who paid agricultural zakat at BAZNAS Kaur Regency. Hypotheses are formulated or tested using multiple regression analysis. The results of this research show that there is an influence on income and trust on interest in paying agricultural zakat.